2015
DOI: 10.2147/opth.s84077
|View full text |Cite
|
Sign up to set email alerts
|

Refractive outcome of prethreshold retinopathy of prematurity treated by diode laser: follow-up at 5 years

Abstract: BackgroundThe purpose of this study was to evaluate the refraction of eyes treated with diode laser photocoagulation for prethreshold retinopathy of prematurity (ROP) at a mean of 5 years after treatment.Materials and methodsFifty infants with prethreshold ROP treated with diode laser at Hanoi Childrens’ Hospital during the period 2008 to 2009 were reviewed. Refractive error was identified by cycloplegic refraction with Cyclogyl 1%. Myopia was divided into two categories based on magnitude: high myopia (more t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
16
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 19 publications
3
16
0
1
Order By: Relevance
“…High prevalence of refractive errors, mainly myopia and high myopia are main functional disturbances not only in threshold [15], [18] but in prethreshold ROP laser treated infants [5], [6], [19], [20]. In our study the mean spherical equivalent for the whole group was -1.82 D, which is similar to the results of Kuo et al, (-1.71) [21], Lolas et al, (-1.75 D) [22] and Nguyen et al, (-2.87 D) [12]. Higher SE values than ours were reported in many other studies.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…High prevalence of refractive errors, mainly myopia and high myopia are main functional disturbances not only in threshold [15], [18] but in prethreshold ROP laser treated infants [5], [6], [19], [20]. In our study the mean spherical equivalent for the whole group was -1.82 D, which is similar to the results of Kuo et al, (-1.71) [21], Lolas et al, (-1.75 D) [22] and Nguyen et al, (-2.87 D) [12]. Higher SE values than ours were reported in many other studies.…”
Section: Discussionsupporting
confidence: 88%
“…These results are similar to the squint rate of ETROP study [16] and lower than data reported by Stoica et al, (46.15%) and Sahni et al, (50%) [7], [17]. Very low strabismus rate was found by Katoch et al, (8.3%) and Nguyen et al, (10%) [12], [13]. These big differences between different studies can be mainly explained with the different follow-up time, but all show that esotropia is the main type of strabismus.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The study depicted the long-term outcome in children treated for ROP with laser therapy. Comparison among the studies[11121314151617] about the patient characteristics are tabulated in Table 4. All the studies including the present study had much higher mean birth weight and mean gestational age compared to ETROP cohort [(703 g) and (25 weeks)].…”
Section: Discussionmentioning
confidence: 99%
“…Specifically for high myopia, laser has been regarded as a risk factor, while anti-VEGF has been regarded as a protective factor [ 11 , 15 ]. Many specialists highlighted the need of long-term follow-up, especially in laser-treated patients [ 34 , 35 ]. However, Kuo et al [ 30 ] found no significant difference in the myopic status of eyes that were treated with either anti-VEGF (27 eyes) or laser (26 eyes).…”
Section: Discussionmentioning
confidence: 99%